2020
DOI: 10.1177/1043986219894420
|View full text |Cite
|
Sign up to set email alerts
|

“You’d Just Cop Flak From Every Other Dickhead Under the Sun”: Navigating the Tensions of (In)visibility and Hypervisibility in LGBTI Police Liaison Programs in Three Australian States

Abstract: This article examines the different ways that lesbian, gay, bisexual, transgender, and intersex (LGBTI) police liaison officers in three states of Australia conceptualized and problematized the public visibility of LGBTI police liaison services. In a climate where LGBTI police liaison services are a prominent model for building relationships between police and LGBTI people, this article considers, through interview data with LGBTI police liaison officers, these officers’ perceptions of the role that the visibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Consistent with this, previous studies in the US and Australia have found that the LGBTQ+ community continues to have disproportionately negative experiences with police with the potential to negatively impact on help-seeking for drug-related problems [19,20]. While there are notable examples of initiatives aimed at improving this relationship [21,22], our findings suggest a more concerted effort is required.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this, previous studies in the US and Australia have found that the LGBTQ+ community continues to have disproportionately negative experiences with police with the potential to negatively impact on help-seeking for drug-related problems [19,20]. While there are notable examples of initiatives aimed at improving this relationship [21,22], our findings suggest a more concerted effort is required.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, participants reported that LGBTQ liaison officers were rarely present to mediate their interactions with police. Indeed, these oftentimes solitary officers are often unable to significantly change their colleagues' views towards LGBTQ civilians (see Dwyer & Ball, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Participants who reported explicit forms of police discrimination were either persons of color or transgender, which may reflect the biased policing of both communities of color (Molla, 2021;Majavu, 2020;Murphy et al, 2018) as well as transgender individuals (Dwyer & Ball, 2020;Miles-Johnson, 2021). For example, Yazid, a participant of mixed South and Western-Asian descent, reported witnessing a thinly concealed outburst from one of the officers attending his domestic violence complaint.…”
Section: Law Enforcement Officersmentioning
confidence: 99%
“…By not gathering or reporting SOGI data, the authors avoided potentially outing LGBTQ participants who may be one of few out LGBTQ people in their sample. As explained by Dwyer and Ball (2020), navigating visibility is a safety issue:…”
Section: Intersectional Representation Of Lgbtq Topics and Individualsmentioning
confidence: 99%